Leptin levels in fetoplacental tissues from normal pregnant women and women with pregnancy-induced hypertension - Bakar, Asiah Abu; Romli, Aminah Che; Singh, Harbindar Jeet (2002)
Leptin has been implicated in a number of obstetrical and gynecological diseases (1).Serum leptin levels have been shown to be significantly higher in pregnant women when compared to non-pregnant obese women (2).The precise source of the extra leptin remains unclear although the placenta has been suggested as the additional source of this leptin.The role of leptin in pregnancy-induced hypertension remains unknown.As the abnormality in PIH is presumed to lie in the placenta we therefore measured the levels of leptin in fetoplacental tissues from normal women and women with pregnancy-induced hypertension (PIH).Four grams each of amnion,chorion leave and placenta were carefully dissected from fresh, vaginally delivered placenta from normal women (n=25) and women with PIH (n=9). After thorough rinsing with Krebs Heinslet buffer pH 7.4, at room temperature,the tissues were blot-dried on a filter paper.Two grams of each of the tissues was individually homogenized in 2 ml of Krebs Heinslet, pH 7.4 for 2 minutes.Following centrifugation for 20 minutes at 4,000 rpm in a refrigerated centrifuge, the supernantant was remove.After that the pellet was re-suspended in the same buffer, re-homogenized, centrifuged and the two lots of supernatants were pooled and stored at 70°C for analysis at a later date. Leptin in the extracts was determined using commercially available RIA Kits. Statistical analysis was performed using Student's 't' test for unpaired observations. Leptin concentration in the placenta was significantly higher in both the groups when compared to its concentration in the corresponding chorion leave and amnion (p<0.01).There were no significant differences in the leptin concentrations between the chorion leave and amnion in either of the two groups.Leptin concentration in the amnion was highly correlated with that in the chorion leave in both the groups (p = 0.000). Similarly, placental leptin also correlated significantly with that in the chorion leave and amnion (p = 0.001). Leptin concentration in the amnion and chorion leave from women with PIH was significantly higher when compared to that in similar tissues from normotensive women (p<0.05).In conclusion, our observations confirm the presence of leptin in the fetoplacental tissues.More significantly however, leptin concentration in tissues from women with PIH appears somewhat higher, particularly in the amnion and the chorion laeve.The significance and the reasons for this remain uncertain and further studies are needed to ascertain the role of leptin in PIH.